2014
DOI: 10.2807/1560-7917.es2014.19.28.20856
|View full text |Cite
|
Sign up to set email alerts
|

Large number of imported chikungunya cases in mainland France, 2014: a challenge for surveillance and response

Abstract: During the summer of 2014, all the pre-requisites for autochthonous transmission of chikungunya virus are present in southern France: a competent vector, Aedes albopictus, and a large number of travellers returning from the French Caribbean islands where an outbreak is occurring. We describe the system implemented for the surveillance of chikungunya and dengue in mainland France. From 2 May to 4 July 2014, there were 126 laboratory-confirmed imported chikungunya cases in mainland France.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 9 publications
(9 reference statements)
2
52
0
3
Order By: Relevance
“…Transmission in this area seems to be only possible during the warm seasons. The vector is spreading to new areas, as reported in France [67,68], where a recent study confirmed the high efficiency of temperate Ae. albopictus to transmit CHIKV [69•].…”
Section: Epidemiology Of Chikv By Continentsupporting
confidence: 52%
See 2 more Smart Citations
“…Transmission in this area seems to be only possible during the warm seasons. The vector is spreading to new areas, as reported in France [67,68], where a recent study confirmed the high efficiency of temperate Ae. albopictus to transmit CHIKV [69•].…”
Section: Epidemiology Of Chikv By Continentsupporting
confidence: 52%
“…The Caribbeans are an area with frequent connecting flights among the islands and to mainland America and Europe, considering that more than 10 million international visits are reported each year by WTO, of which 25 % from Europe [77]. In fact, in 2014, a significant increase of CHIVK imported cases from the Caribbeans was reported in France and in Spain [68,78]. Local transmission of CHIKV in the Caribbeans was very effective.…”
Section: Epidemiology Of Chikv By Continentmentioning
confidence: 99%
See 1 more Smart Citation
“…In October 2013, two laboratory-confirmed, autochthonous CHIKV cases were detected in the French territory of Saint Martin Island, in the Caribbean Sea (102). Surprisingly, the CHIKV strain isolated belonged to the Asian genotype rather than (20,58,109).…”
Section: Vectorsmentioning
confidence: 99%
“…The mosquito vector, Aedes albopictus, first introduced in southern France in 2004, was established in 18 districts in 2014 [3]; and the virus is regularly introduced by viraemic travellers returning from endemic or epidemic countries to mainland France where the population is naive for chikungunya virus (CHIKV). This situation led to a first episode of autochthonous transmission of chikungunya in south-east France in 2010 [4].…”
Section: Introductionmentioning
confidence: 99%